2017
DOI: 10.1016/j.cmi.2017.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of teicoplanin and attainment of pharmacokinetic/pharmacodynamic targets in adult patients with haematological malignancy

Abstract: 19Objectives: To describe the population pharmacokinetics of teicoplanin in adult haematological 20 malignancy patients receiving higher than standard doses and to perform Monte Carlo simulations 21 to determine dosing regimens associated with optimal teicoplanin concentrations. 22Methods: This was a hospital-based clinical trial (EudraCT 2013-004535-72). Nine blood samples 23 were collected on Day 3, plus single trough samples on Days 7 and 10, and 24 and 48 h post last 24 dose. Teicoplanin minimum inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 29 publications
2
39
1
1
Order By: Relevance
“…12,[14][15][16][17]25,46,47 The final estimated value of CL (0.59 L/h) was not significantly different from the values in previous studies (CL 0.3-2.0 L/h), and the estimated value of Vd area (144 L/70 kg) was slightly larger than those of previous studies (40-110 L/70 kg). 12,[14][15][16][17]25,46,47 In the present study the volume of distribution was corrected based on the standard FFM of 56.1 kg (assumed TBW of 70 kg and height of 1.76 m). This was considered 1 of the reasons for the larger Vd area of the present study: no previous studies had evaluated the influence of FFM.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…12,[14][15][16][17]25,46,47 The final estimated value of CL (0.59 L/h) was not significantly different from the values in previous studies (CL 0.3-2.0 L/h), and the estimated value of Vd area (144 L/70 kg) was slightly larger than those of previous studies (40-110 L/70 kg). 12,[14][15][16][17]25,46,47 In the present study the volume of distribution was corrected based on the standard FFM of 56.1 kg (assumed TBW of 70 kg and height of 1.76 m). This was considered 1 of the reasons for the larger Vd area of the present study: no previous studies had evaluated the influence of FFM.…”
Section: Discussioncontrasting
confidence: 59%
“…12,[14][15][16]25,46,47 The teicoplanin concentrations were mainly collected in the elimination phase, with some being from the distribution phase (Figure 1). 12,[14][15][16]25,46,47 The teicoplanin concentrations were mainly collected in the elimination phase, with some being from the distribution phase (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnosis for each infection was based on de nitions in the guidelines issued by the National Healthcare Safety Network [13]. Infections with at least one of the following signs were analyzed: core temperature >37.8°C, total peripheral white blood cell (WBC) count >10,000/mm 3 , or C-reactive protein (CRP) >3.0 mg/dL.…”
Section: Patientsmentioning
confidence: 99%
“…For bone and joint infections and infective endocarditis, teicoplanin 12 mg/kg body weight every 12 h for three-to-ve doses is recommended [6]. In Monte Carlo simulations, a high probability of attaining the target C min of 20 μg/mL was observed using a regimen of 12 mg/kg administered at 12-h intervals for ve doses, but not when using four doses [13]. Byrne et al [14] reported the recommended loading dose to achieve a C min ≥20 μg/mL based on population PK analysis was 12 mg/kg administered every 12 h for ve doses in patients with a body weight of 70 kg and serum albumin level of 3.0 mg/dL.…”
Section: Introductionmentioning
confidence: 99%